Keefektifan Model Pembelajaran Think Pair And Share Pada Materi Macam-Macam Gaya Kelas IV MIN 1 Gresik - Siti Nur Afifah; Mulyadi (El-Miaz: Jurnal Pemikiran dan Pendidikan Dasar, 2021)
The problem of education in Indonesia, one of which is still dwelling on the issue of quality and quality of education. Indonesia is still far behind in the quality of education compared to other countries in the world. The low quality of education results in the low quality of human resources. If the quality of human resources is low, it will be difficult to live in the current era of globalization. Group-based learning model seems to be an alternative to the problem of low learning outcomes. One of them is by applying the think pair and share learning model to a variety of styles. Therefore, the formulation of the problem in this study is how effective is the think pair and share learning model in the various styles of class IV MIN I Gresik?. The data collection techniques are interviews, observation, questionnaires (questionnaires), documentation and learning outcomes assessment tests. The instruments of this research are learning instrument validation, learning outcome assessment test validation, teacher ability observation sheet to process learning, student activity sheet, student response questionnaire and learning outcome assessment test. The data analysis method used is the average, percentage formula, test item validity using the product moment formula (rxy), item sensitivity and item reliability. The results of the study show that the first is the ability of teachers to process learning in the experimental class an average of 93% which is in the Good criteria and in the control class an average of 82% which is in the Good criteria, the second is the analysis of student activity data in the experimental class obtained an average of 82%. an average of 91% which is in the Good criteria and in the control class an average of 37% is in the Enough criteria, the third analysis of student response data is said to be positive with the Agree category, the fourth analysis of learning outcomes assessment data (PHB) obtained completeness classical learning of the experimental class by 87% and the control class by 30% and the assessment of learning outcomes (PHB) fulfilled the validity, reliability, and sensitivity tests.